2023
DOI: 10.1111/1541-4337.13112
|View full text |Cite
|
Sign up to set email alerts
|

A review of the structure, function, and application of plant‐based protein–phenolic conjugates and complexes

Abstract: Interactions between plant‐based proteins (PP) and phenolic compounds (PC) occur naturally in many food products. Recently, special attention has been paid to the fabrication of PP–PC conjugates or complexes in model systems with a focus on their effects on their structure, functionality, and health benefits. Conjugates are held together by covalent bonds, whereas complexes are held together by noncovalent ones. This review highlights the nature of protein–phenolic interactions involving PP. The interactions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 141 publications
0
26
0
Order By: Relevance
“…To date, various plant-based proteins derived from cereals, legumes, pulses, oilseeds, and nuts have been trialled to replace animal proteins as stabilising, foaming, thickening and gelling agents. 16,17 The contemporary food industry uses an alkaline extraction-isoelectric precipitation method to extract these (plant and algae-based) proteins, whereby the protein is solubilised in the alkali solution and precipitated around its isoelectric point, followed by separation and drying. 17 The precipitation process causes molecule aggregation and folding, producing a protein with an increased size and compact structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, various plant-based proteins derived from cereals, legumes, pulses, oilseeds, and nuts have been trialled to replace animal proteins as stabilising, foaming, thickening and gelling agents. 16,17 The contemporary food industry uses an alkaline extraction-isoelectric precipitation method to extract these (plant and algae-based) proteins, whereby the protein is solubilised in the alkali solution and precipitated around its isoelectric point, followed by separation and drying. 17 The precipitation process causes molecule aggregation and folding, producing a protein with an increased size and compact structure.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 The contemporary food industry uses an alkaline extraction-isoelectric precipitation method to extract these (plant and algae-based) proteins, whereby the protein is solubilised in the alkali solution and precipitated around its isoelectric point, followed by separation and drying. 17 The precipitation process causes molecule aggregation and folding, producing a protein with an increased size and compact structure. In addition, plant-based proteins are commonly composed of multiple protein fractions with a high molecular weight and globular structure (e.g., albumins, globulins, glutelins, and prolamins).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that phenolic compounds can interact with proteins through non-covalent bonds (hydrophobic interactions and hydrogen bonds), which are generated spontaneously in most food systems. It has been described that the interaction positively influences the sensory, functional, and antioxidant properties of food products [ 23 , 24 ]. For that, chickpea proteins could interact with polyphenols, which can help to protect the antioxidant capacity of phenolic compounds extracted from the walnut green husk and be used to develop new natural food additives.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the formation of complexes between polyphenols and proteins, such as peanut and cashew proteins, has been shown to prevent antibody recognition of allergens via allergen precipitation and reduce IgE binding to allergens [ 5 , 6 , 7 ]. Plant-based proteins (PP)–phenolic compounds (PC) conjugates and complexes have been reported to exhibit potential allergy-reducing activities [ 8 ]. The regulation of gut microbiota by polyphenols might also contribute to their anti-allergic/-inflammatory properties [ 2 ].…”
Section: Introductionmentioning
confidence: 99%